Spatial and temporal use of a tropical nursery habitat by juvenile blacktip sharks (Carcharhinus limbatus) - Lauren A. Moe; Jason P. Turner; Jay R. Rooker; R. J. David Wells; Steven L. Colbert (Frontiers in Marine Science, 2026)
Blacktip sharks ( Carcharhinus limbatus ) are a circumglobal species that rely on nearshore nursery habitats during their early years. Movement patterns and habitat use of blacktip sharks in the Hawaiian Islands is poorly understood, and no nursery habitats have been discovered within Hawai’i. For this study, juvenile blacktip sharks (n = 29) were caught and tagged in Hilo Bay, Hawai’i, USA with acoustic transmitters. Tracking occurred every 2–5 weeks between July 2022 and January 2024 at 44 stations throughout Hilo Bay using a receiver and omnidirectional hydrophone. Results showed that juvenile blacktip sharks were present in the bay year-round, with the greatest monthly residence (41.3-50.0%) from March through August, and the lowest monthly residence (24.1-30.1%) from October through January. Blacktip sharks were detected within Hilo Bay more during the day than at night, but more frequently in deeper waters at night, which is likely due to excursions into deeper waters during heightened nocturnal foraging activity. Temperature and salinity did not significantly vary among stations, and as such, were not influential factors in habitat use. Dissolved oxygen (DO) appeared to limit habitat use during the day when concentrations were lowest in the bay. The lowest DO concentrations were observed during the months when the fewest number of sharks were detected, suggesting that oxygen requirements may influence habitat use within the bay. The residency patterns presented here support the delineation of Hilo Bay as the first known blacktip shark nursery habitat in Hawaiian waters. Our results suggest that this population of blacktip sharks reside predominantly within Hilo Bay for the first few years of their life, and highlight the effect that environmental changes can have on this species’ habitat availability and movement patterns.